APLIKASI ENKRIPSI CITRA DIGITAL BERBASIS CHAOS MENGGUNAKAN ALGORITMA ARNOLD’S CAT MAP - Rama Dian Syah; Antonius Angga Kurniawan; Rizki Ariyani (Jurnal Ilmiah Teknik, 2022)
The rapid development of technology can lead to vulnerabilities in data and information. Everyone can access that data and information and disseminate it easily through the internet. The data and information can be in the form of text, video, audio, and images that may be confidential. To prevent misuse and unauthorized access to this confidential data and information, a technique is needed to enhance the security of the data. One of these techniques is by encrypting data. This technique is used to encode data in such a way that the security of the information is maintained and it cannot be read without being decrypted first. The encryption technique that has been developed involves implementing chaos theory, one of which uses the Arnold’s Cat Map algorithm. This algorithm is applied in the process of encrypting and decrypting digital images with png and bmp extensions. The results of this trial show that the image files can be encrypted and decrypted properly. The time obtained is directly proportional to the size of the image.